Fracture Resistance and Failure Modes of Lithium Disilicate or Composite Endocrowns - DALKILIÇ, EVRİM; Altıer, Muhammed; Erol, Funda; Yıldırım, Gulhan; DALKILIÇ, EVRİM (My University, 2018)
Purpose: The aim of this study was to determine the fracture strength of endocrowns made of lithium disilicate ceramic and two different indirect resin composites. Materials and Methods: Forty human mandibular molars were randomly separated into four groups (n = 10 in each group) -Group IN: control group, Group IPS: endocrowns made of lithium disilicate ceramic (IPS e. max CAD, IvoclarVivadent, Schaan, Liechtenstein); Group SL: Endocrowns made of Solidex microhybrid composite (Shofu, Ratingen, Germany); and Group GR: Endocrowns made of Grandia microhybrid composite (GC Europa, Leuven, Belgium). In all of the groups, dual-cure resin cement (Relyx Ultimate Clicker, 3M ESPE, St. Paul, MN, USA) was used to cement the endocrowns. All of the teeth were subjected to fracture by means of a universal testing machine (Instron), and compressive force was applied. The failure type and location after fracture were classified. The data were analyzed using one-way ANOVA, Tukey-s post hoc test, and Chi-square test (P 0.05). In Group SL, 80% of the specimens exhibited favorable fractures; also, 60% of the specimens exhibited favorable fracture in group GR, and only 10% of the specimens exhibited favorable fracture in group IPS. Conclusions: The lithium disilicate ceramic endocrowns exhibited higher fracture resistance than indirect composite groups. Both of the composite endocrowns showed more favorable failure than the lithium disilicate ceramic endocrowns.
Keywords: Fracture Resistance